Pembelajaran Think Pair Share (TPS) dipadu Pendekatan Sainstifik untuk meningkatkan hasil belajar IPA pada siswa kelas VIII SMP Islam Samargalila Labuha Halmahera Selatan - Harun Ibrahim; Dharmawaty M Taher; Ade Haerullah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Many efforts have been made by the government to improve the quality of education in schools as a top priority, one of the efforts that can be taken is to improve the quality of the learning process. Improving the quality of the learning process can be done by increasing the potential of the teacher as one of the elements in the learning process. The purpose of this research is to obtain social attitudes and learning outcomes of students with the think pair share (TPS) cooperative learning model combined with scientific additive material. and addictive substances in food and drink in class VIII Islamic Middle School Samargalila Labuha Halmahera Selatan. The design and type of research used was a quasi-experimental consisting of two classes with a one group pretest-posttest research design. The results of the study show that the TPS learning model combined with a scientific approach has more potential to improve student learning outcomes. This is evidenced by an increase in the average student learning outcomes before treatment from 40.84 to 73.06. Thus, it can be concluded that the TPS combined scientific model has more potential to improve students' cognitive learning outcomes.